Inflammatory profiling and immune cell infiltration in dysthyroid optic neuropathy: insights from bulk RNA sequencing - Qintao Ma; Yuanping Hai; Yongbo Duan; Genfeng Yu; Cheng Song; ShengAi Huang; Anqi Huang; Yan Zhu; Yongzhi Shen; Zimeng Huang; Xiao Wang; Lan Liu; et al. (Frontiers in Immunology)
BackgroundDysthyroid optic neuropathy (DON), the most severe complication of thyroid eye disease (TED), has unclear mechanisms and unsatisfactory treatment outcomes. This study aimed to identify key pathways and inflammation-related core genes driving DON progression, potentially informing new therapeutic strategies and improving disease management.MethodsRetro-orbital tissues from DON, non-DON TED, and healthy controls (HCs) were analyzed using bulk RNA sequencing. Differentially expressed genes (DEGs) were identified and subjected to Gene Ontology (GO) enrichment analysis. Weighted gene co-expression network analysis (WGCNA) identified disease-relevant modules. Immune cell infiltration was assessed via single-sample Gene Set Enrichment Analysis (ssGSEA). ROC analysis and single-gene GSEA were used to evaluate the diagnostic potential and functional relevance of core genes. Inflammatory-Related Differential Genes (IRDGS) were identified and preliminarily validated using Quantitative Real-Time PCR.ResultsDifferential gene expression analysis revealed 176 and 202 significantly upregulated genes in DON vs. non-DON and DON vs. HCs comparisons, respectively. Notably, inflammation-related genes, including CXCL14, CCL21, HP, and fibrosis-associated genes such as MGP, FN1, and COL11A1, were significantly upregulated in DON group. GO enrichment analyses identified immune-related processes like lymphocyte proliferation, cytokine activity, and extracellular matrix remodeling. WGCNA further identified key gene modules associated with inflammation and tissue remodeling in DON, and IRDCGs, such as CCL21, HP, and SLCO2A1, emerged as the most significant markers. Single-gene GSEA confirmed that these genes are involved in immune response, inflammation, and fibrosis-related processes. Immune cell infiltration analysis using ssGSEA revealed that DON patients exhibited significantly increased infiltration of activated B cells, CD4 T cells, mast cells, and Th1 cells, and correlation analysis showed that IRDGs were significantly associated with multiple immune cell types, particularly activated B cells and regulatory T cells. Finally, qPCR validation of the top 10 IRDEGs in retro-orbital tissues showed that HP, TPSAB1, and PLA2G2A were significantly upregulated in the DON.ConclusionsThis is the first study to identify the key molecular and immune drivers of DON through bulk transcriptomic analysis, emphasizing the central role of inflammation-related molecules and immune cell infiltration in its pathogenesis. The identified IRDGs and their associated pathways provide novel insights for innovative diagnostic and therapeutic strategies.